From conflict to cooperation : Labour market reforms that can work in Nepal. - Office, International Labour (International Labour Office, 2008)
This book reviews the history of labour relations in Nepal and considers criticisms of the existing industrial relations system. It reports on the re-emergence of the militant Maoist trade union and the recent upsurge in strikes and demonstrations in Nepal. A reduction in workplace tension is required to cement in place the recent peace agreement, facilitate political stability and promote economic growth.